2015
DOI: 10.4088/jcp.14m09365
|View full text |Cite
|
Sign up to set email alerts
|

Does Acute Stress Disorder Predict Subsequent Posttraumatic Stress Disorder in Pediatric Burn Survivors?

Abstract: The prevalence of PTSD was similar in children who had ASD symptoms and those without ASD symptoms. The lifetime prevalence of PTSD was lower than reported in other studies. A possible explanation for this finding is that children received timely pharmacotherapy and psychotherapy during their acute hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…Of the 16 studies reviewed, 10 referred to the aggravating factors [12][13][14][15][16][17][18][19][20][21] (table 1) and the remaining 6 were related to the assessment tools (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 16 studies reviewed, 10 referred to the aggravating factors [12][13][14][15][16][17][18][19][20][21] (table 1) and the remaining 6 were related to the assessment tools (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This study concluded that clinically elevated PTSD symptom levels were more frequent in children admitted for traumatic injuries (18%) than illness/medical-related causes (4%) and there was a significant relationship (positive) between length of stay and the development of PTSD. Another study 13 examined the prevalence of PTSD in pediatric burn survivors who had been treated for acute stress disorder (ASD) symptoms during their initial hospitalization and compared them with patients who had been asymptomatic for ASD symptoms and found that the prevalence of PTSD was similar in children with ASD symptoms and those without ASD symptoms.…”
Section: Aggravating Factorsmentioning
confidence: 99%
“…And opioid tolerance/habituation is a challenge for patients with large severe burns (Bittner et al, 2015), who typically receive the same painful procedures over and over, several times per week, often daily, during several weeks of hospitalization. Excessive pain and/or repeated high opioid doses can pathologically alter the patients pain perception system, disrupting the patient's natural endogenous opioid analgesia system (Schwaller and Fitzgerald, 2014; Ballantyne, 2018; Chambers, 2018), and can increase patient's risk of developing chronic pain, anxiety disorders, and/or Post-Traumatic Stress Disorder (McGhee et al, 2011; Rosenberg et al, 2015, 2018; Pardesi and Fuzaylov, 2017; Peña et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recovering from a large severe burn injury involves intense medical treatments such as repeated painful wound cleaning sessions, skin graft surgeries, and physical therapy skin stretching exercises (Hoffman et al, 2011 ). Patients who have sustained a large severe burn are at increased risk of developing psychological disorders such as depression, anxiety, post-traumatic stress disorder, social anxiety, and apprehension about their changed appearance (Meyer et al, 2007 , 2012 ; Stoddard et al, 2011 ; Rosenberg et al, 2015 ). Burn patients often report an increase in negative thoughts and emotions, and a decrease in positive thoughts/emotions (Meyer et al, 2012 ; Murphy et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients may experience intense negative emotions such as guilt (e.g., survivor guilt) or shame when thinking about the burn injury. They also may have recurring flashbacks about the accident and this can cause a patient to feel sad, angry, or afraid (Meyer et al, 2007 ; Rosenberg et al, 2015 ). Further, patients with large severe burns are often hospitalized for weeks or months while they recover from their burn injury.…”
Section: Introductionmentioning
confidence: 99%